2010
DOI: 10.1577/c09-046.1
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Growth Differences and the Influence of Diet Quality on Atka Mackerel of the Aleutian Islands, Alaska: Using a Bioenergetics Model to Explore Underlying Mechanisms

Abstract: Atka mackerel Pleurogrammus monopterygius make up the single largest biomass of groundfish in the Aleutian Islands, Alaska, and are an important component of this marine ecosystem. Atka mackerel show a significant decrease in size from east to west. We compared fish from two study areas reflecting this size cline: Seguam Pass in the eastern Aleutians and Amchitka Island in the western Aleutians. At any given age, the Atka mackerel at the former location are larger than those at the latter (e.g., 5‐year‐old fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…These results might reflect differences in environmental conditions between these areas. Seguam Pass has been shown to provide better quality food for Atka mackerel than Amchitka Island (Rand 2007). Lower overall growth rates at Amchitka and lower weight at length seem to further support the hypothesis that fish there have less energy available for growth and reproduction once they reach adult sizes.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…These results might reflect differences in environmental conditions between these areas. Seguam Pass has been shown to provide better quality food for Atka mackerel than Amchitka Island (Rand 2007). Lower overall growth rates at Amchitka and lower weight at length seem to further support the hypothesis that fish there have less energy available for growth and reproduction once they reach adult sizes.…”
Section: Discussionmentioning
confidence: 74%
“…The captive fish in this study were generally fed to satiation three times per week. In wild fish, food consumption peaks in the summer but declines by October, when the majority of stomach samples are empty (Rand 2007). Rand (2007) found that the fish at Amchitka Island generally consume less food and lower-quality food than those at Seguam Pass and linked the growth rates observed in those areas to food consumption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Rand et al. () found large differences in the diets of Atka Mackerel in the eastern Aleutian Islands (NMFS Area 541) relative to those in the western Aleutian Islands (Figure ; NMFS Area 542), with the former consuming more energetically rich prey. The diel patterns described in the present study should be explored further with respect to Atka Mackerel prey fields across the Aleutian Islands archipelago.…”
Section: Discussionmentioning
confidence: 99%
“…Temporal variation in prey quality, i.e. energy content, could also contribute (Rand et al, 2010). Mackerel prey on a wide size range of prey items (Prokopchuk and Sentyabov, 2006;Langøy et al, 2012;Óskarsson et al, 2016;Bachiller, et al, 2016) of which the larger prey is poorly sampled with WP2-nets (Gjøsaeter et al, 2000).…”
Section: Prey Abundancementioning
confidence: 99%